Zeolite and Organic Fertilizer Application to The Improvement of Available P and Soybean (Glycine max L) Seed Yield in Alfisols - Putri Alvernia; Slamet Minardi; Suntoro Suntoro (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2017)
The problem of low soybean yield on Alfisol is low soil fertility. The availability of P is often a constraint because the P element on the Alfisol soil is strongly bound by Al and Fe elements. Efforts to increase the availability of P element in Alfisols can be done by ameliorant of zeolite and organic fertilizer. This study objective was determined of zeolite and organic fertilizer in increasing of available P and soybean yield on Alfisols. A field experiment was conducted using Randomized Block Design consisting of two factors: a dose of zeolite (0 ton ha-1, 2.5 tons ha-1, and 5 ton ha-1), and organic fertilizer (no organic fertilizer, quail, and cow manure 5 ton ha-1 respectively). The results showed that zeolite 5 ton ha-1 is the highest effect on the increasing of available P, pH, organic matter, and saturation base as big as 5.19, 5.21, 24.03, and 21.55 respectively, while cow manure is improved to organic matter and saturation base 26.17, and 21.38% respectively.The combination of zeolite and cow manure 5 ton ha-1 gave the highest yield on the number of pods (101 pods plants-1), and the 1000 seeds weight is 153 g.